2019
DOI: 10.56093/ijas.v89i10.94576
|View full text |Cite
|
Sign up to set email alerts
|

Research status of bael (Aegle marmelos) in India: A review

Abstract: Bael [Aegle marmelos (L.) Correa ex Roxb., Family Rutaceae] is one of the oldest known fruit tree species native to India. Wide distribution of bael in Indian subcontinent and other parts of the world reflects its adaptation to a range of agro-climatic conditions. In addition to well-known nutritional and traditional medicinal benefits, the bael fruits have considerable processing and industrial values. In order to better utilize and improve the existing genetic resource, there is a need scrutinizing the studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The other results showed that there are secondary metabolites in plants that can be used as a mechanism for interaction between plants and animals, namely phytochemicals [43][44][45], so they can be used as biopesticides, for example papaya leaves. Papaya leaves contain the enzyme papain which when it enters the trachea of insects, then spreads and can interfere with the performance of the nervous system of these insect pests [46].…”
Section: Discussionmentioning
confidence: 99%
“…The other results showed that there are secondary metabolites in plants that can be used as a mechanism for interaction between plants and animals, namely phytochemicals [43][44][45], so they can be used as biopesticides, for example papaya leaves. Papaya leaves contain the enzyme papain which when it enters the trachea of insects, then spreads and can interfere with the performance of the nervous system of these insect pests [46].…”
Section: Discussionmentioning
confidence: 99%
“…Using integrated approach, disease and pest can be managed effectively such as management of aphids, wilt, blight, downy mildew and powdery which are the most detrimental biotic stresses in seed spices [39,48,108]. In order to manage the wilt disease, soil solarization (covering of moist soil with plastic sheets) can be an effective method to kill soil born pathogen which causes wilt.…”
Section: Management Of Agronomical Constraintmentioning
confidence: 99%
“…It is sacred tree in Hinduism, and is offered in prayers of Hindu deities Lord Shiva and Parvati and thus, the tree is also known by the name Shivaduma (The Tree of Shiva). Its medicinal properties have been described in the ancient treatise like Charaka Samhita,Upvana Vinod and Yajur Veda, and it has also been portrayed in the paintings of Ajanta Caves Singh et al [2].…”
Section: Introductionmentioning
confidence: 99%